Social interaction in an online cross-disciplinary research conference - Nyirenda, Tawona Vanessa (Department of Information Systems, 2023)
This research study investigated the social interaction in an online cross-disciplinary research conference. The research study followed an online conference of researchers from disciplines of social sciences, law, and humanities. The online conference was initiated by the National Research Foundation (NRF) and was hosted by Centre for Educational Technology (CET) at University of Cape Town (UCT). The main aim of the research study is to identify social interaction enablers and inhibitors in an online cross-disciplinary conference. The Internet is being used for numerous purposes, such as extending one's social networks, participating in online communities, finding a marriage partner, learning, and developing successful business relationships. An online conference uses the Internet for social networking. The study followed an interpretive research approach and combined critical discourse analysis (CDA) and the social presence indicators template (SPIT) as its analytical framework. The focus of the study was on the analysis and interpretation of the online conference text messages (artefacts) to identify enablers and inhibitors of social interaction. The social interaction enablers identified in the study included sharing and seeking of information, social presence, time and geographical confidence and flexibility, facilitation, prescribed/relevant topics and increased confidence and reduced evaluation anxiety. Inhibitors of social interaction were lack of community, prescribed topics, minimal activities, lack of non-verbal and social cues and clarity of topics. The social interaction enablers that were not identified in the literature were prescribed/relevant topics and collaboration and lobbying. Lack of community, clarity of topics, prescribed topics and minimal activities were identified as inhibitors of social interaction in the study but were not identified in the literature. In addition, the research found that some social interaction enablers were also found to be inhibitors. A revelation in the research study was that prescribed topics both enabled and inhibited social interaction. While some participants contributed towards these topics, others did not. Although the study focused predominantly on a cross-disciplinary research conference the findings reported in this study could have useful applications on online social interaction in general. The study has found out that an online conference arguably has merits over a face-to-face conference, but these benefits can only be optimised when social interaction is deliberately fostered through convergence of the online conference tool, facilitation, and topic design.